2004
DOI: 10.1002/pssa.200303908
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of shallow impurities in GaN studied via bound exciton magnetooptics

Abstract: We report the photoluminescence experiments on high quality GaN samples in high magnetic fields. A detailed analysis of the recombination due to excitons bound to neutral donors and acceptors is presented. Special attention is focussed on transitions for which the impurity is left in the excited state (so called two electron satellites). These results show a rich energetic structure of excited states of the impurity involved in such a recombination process. The magnetic field dependence of the energy structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Taking into account that the binding energy of a shallow donor in GaN is around 30-33 meV [9] and effective Coulomb interaction could be estimated to be in the order of 60 meV [4], the beryllium ionization resulting from the formula (2) is of about 92-95 meV. Since usually optical transition energies are bigger than thermal activation energies of the acceptor centers, the obtained estimation of the Be ionization energy, being in the range of 90-125 meV, seems to be consistent with the results of the temperature dependent luminescence studies.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account that the binding energy of a shallow donor in GaN is around 30-33 meV [9] and effective Coulomb interaction could be estimated to be in the order of 60 meV [4], the beryllium ionization resulting from the formula (2) is of about 92-95 meV. Since usually optical transition energies are bigger than thermal activation energies of the acceptor centers, the obtained estimation of the Be ionization energy, being in the range of 90-125 meV, seems to be consistent with the results of the temperature dependent luminescence studies.…”
Section: Resultsmentioning
confidence: 99%
“…19 Their energy positions are very close to those observed for neutral donor bound excitons in strain-free homoepitaxial layers. 29,30 Magneto-optical studies 31,32 have shown that all three of these lines split in a similar way, typical for the A exciton bound to a neutral donor in GaN. The observed energy difference between emissions in the freestanding GaN and heteroepitaxial layer makes direct comparison of the structures due to oxygen and silicon donors difficult.…”
Section: Zero-field Characteristics Of Principal D 0 X Transitiomentioning
confidence: 99%